Clinical Significance of Neoadjuvant Chemotherapy With Gemcitabine Plus S-1 for Resectable Pancreatic Ductal Adenocarcinoma - SUZUKI, TAKASHI (In Vivo, 2019)
Background/Aim: Little is known about the efficacy of neoadjuvant chemotherapy (NAC) with gemcitabine plus S-1 (GS) for patients with resectable pancreatic ductal adenocarcinoma (R-PDAC). The aim of this study was to investigate differences in the long-term outcome of patients with R-PDAC undergoing pancreatectomy with and without NAC-GS to clarify the clinical significance of NAC-GS. Patients and Methods: A total of 77 patients with R-PDAC who were scheduled for pancreatectomy between January 2012 and December 2017 were enrolled. Of these patients, 39 received NAC-GS (GS group) and 38 had upfront surgery (UFS group). Results: Among the 77 patients, one patient in each group did not undergo pancreatectomy due to intraoperative non-curative factors. Median tumor size and the number of lymph nodes with metastasis were significantly lower in the GS group than in the UFS group (p=0.002 and p=0.017). However, the 5-year overall survival rate was similar in the two groups (26.1% versus 21.5%, p=0.930). Conclusion: NAC-GS may not be recommended for patients with R-PDAC since it does not seem to offer any survival benefits.